Construction and Optimisation of Economic Performance Evaluation Systems in Project Management: A Mixed-Method Approach From the Perspective of Construction Enterprises - Huabin Yang; Zheng Yang (Buildings)
In the current context of economic globalisation and intensifying market competition, refined management of construction projects is crucial, particularly regarding economic performance management, which directly impacts the stable development of construction companies. Most existing studies evaluate performance using a single research method. This paper combines qualitative and quantitative research methods and integrates a comprehensive, scientific, rigorous economic performance analysis system with multi-criteria decision-making. First, utilising numerous journal articles, interview data, book materials, and 407 questionnaire responses, a preliminary economic performance analysis system for engineering project management was developed through three-level coding using grounded theory. Subsequently, a factor analysis was employed to select indicators for the analysis system, resulting in an evaluation framework for the economic performance of engineering project management with eight core assessment indicators. Finally, based on the evaluation system, the relationships between the indicators and the calculation formulas for the three-level indicators were summarised, culminating in a closed-loop, systematic, and multi-dimensional analysis framework. This study enhances the evaluation framework for the economic performance dimension in engineering project management within construction enterprises. It provides robust methodological and data support for assessing economic performance in engineering project management.